Investigation of fabric stiffness on tencel fabrics in terms of clothing comfort - (:unkn) unknown (Fiber Society, 2012)
Besides durability, design and fashionable, also, today fabric handling and comfort of a cloth are becoming into prominence. In general, consumers prefer a ready-made product by looking its softness-stiffness, hand, glossiness, and drape in other words its comfort properties. Fabric stiffness is one of the most widely used parameter to judge bending rigidity and fabric handling. The degree of fabric stiffness is related to its properties such as fiber material, yarn and fabric structure. But if it is a readymade product, also the sewing parameters should be taken into consideration [1]. In this work, the effects of several sewing parameters such as seam allowance and seam density on fabric stiffness have been investigated. As fabric, tencel (100%) and tencel/linen (70/30%) were chosen because nowadays tencel fabric is widely used in ready-made industry especially for daily outwear cloths. As stitch type lock stitch was used in all samples. Three different seam allowances and three different seam densities were used. By using these fabrics and sewing parameters, 18 different combinations were formed. Then, samples' fabric stiffness was tested according to ASTM D1388-08 standard namely "Standard Test Method for Stiffness of Fabrics" and results were evaluated in terms of sewing parameters with graphs.
Keywords: Fabric stiffness; Sewing parameters; Tencel fabric